Changes in lumbar multifidus muscle function and nociceptive sensitivity in low back pain patient responders versus non-responders after dry needling treatment. Issue 6 (December 2015) - Koppenhaver, Shane L.; Walker, Michael J.; Su, Jonathan; McGowen, Jared M.; Umlauf, Lindsey; Harris, Kevin D.; Ross, Michael D.
Abstract: Background: Little is known about the physiologic mechanism of dry needling. While some evidence suggests that dry needling may decrease nocioceptive sensitivity and facilitate muscle function, no studies to date have examined these physiologic changes compared to clinical outcomes. Objective: To examine changes in lumbar multifidus (LM) muscle function and nociceptive sensitivity after dry needling in patients with LBP and to determine if such changes differ in patients that exhibit improved disability (responders) and those that do not (non-responders). Design: Quasi-experimental study. Methods: Sixty-six volunteers with mechanical LBP (38 men, age = 41.3 ± 9.2 years) completed the study. Ultrasound measurements and pain algometry of the LM were taken at baseline and repeated immediately following dry needling treatment to the LM muscles and after one week. The percent change in muscle thickness from rest to contraction was calculated for each time point to represent muscle function. Pressure pain threshold (PPT) was used to measure nociceptive sensitivity. Participants were dichotomized as responders and non-responders based on whether or not they experienced clinical improvement using the modified Oswestry Disability Index after one week. 2 × 3 mixed-model ANOVA were conducted for group (responders vs. non-responders) by time. Results: Patient responders exhibited larger improvements in LM muscle contraction and nociceptive sensitivity 1 week, but not immediately, after dry needling than non-responders. Conclusions: Our results suggest that there may be lasting and clinically relevant sensorimotor changes that occur in LBP patients that improve with dry needling treatment that partially explain the physiologic mechanism of action. Highlights: Dry needling may facilitate lumbar multifidus contraction in patients with LBP. Dry needling may improve nociceptive sensitivity in patients with LBP. Responders to dry needling may exhibit different physiologic changes than non-responders. These sensorimotor changes may partially explain the mechanism of action of dry needling.